2018
DOI: 10.36984/jkm.v1i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Latihan Fisik Jalan Kaki Terhadap Penurunan Kadar Gula Darah Pada Penderita Dm Tipe Ii Di Kelurahan Kubu Dalam Parak Karakah Wilayah Kerja Puskesmas Andalas Padang

Abstract: Penyakit DM Tipe II adalah suatu keadaan hiperglikemia yang disebabkan gangguan pada resistensi insulin dan sekresi sehingga metabolisme tubuh juga terganggu. Pada DM Tipe II latihan fisik berperan sebagai pengatur dan mampu mengendalikan kadar gula darah. Salah satu latihan fisik yang dianjurkan pada pasien DM Tipe II adalah olahraga jalan kaki. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh latihan fisik jalan kaki terhadap penurunan kadar gula darah pada pasien DM Tipe II. Penelitian ini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The evaluation results from this systematic review found that walking was the most studied type of physical exercise, namely 18 studies (42%) with all of the studies showing a significant effect of walking on decreasing blood glucose levels. As in the research conducted by Rehmaita & Tahlil (2017), Gainey et al (2016), Hikmasari & Sari (2016), Amelia et al (2018) and Mitranun et al (2014). There was a decrease in blood glucose levels after the buddhist walking meditation and traditional walking groups, with mild changes in intensity from light intensity at weeks 1-6 to moderate intensity at weeks 7-12 (Gainey et al, 2016).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The evaluation results from this systematic review found that walking was the most studied type of physical exercise, namely 18 studies (42%) with all of the studies showing a significant effect of walking on decreasing blood glucose levels. As in the research conducted by Rehmaita & Tahlil (2017), Gainey et al (2016), Hikmasari & Sari (2016), Amelia et al (2018) and Mitranun et al (2014). There was a decrease in blood glucose levels after the buddhist walking meditation and traditional walking groups, with mild changes in intensity from light intensity at weeks 1-6 to moderate intensity at weeks 7-12 (Gainey et al, 2016).…”
Section: Resultsmentioning
confidence: 62%
“…Likewise, interval and continuous walking exercises were carried out for 12 weeks with gradual changes in intensity, from moderate in the first week and vigorous in the second and third weeks (Mitranun et al, 2014). Research by Amelia et al (2018) found that walking exercise with a frequency of 3 times/week for 3 weeks and a duration of 30-60 minutes showed the effect of decreasing blood glucose, in the first week there was a decrease of 9.16 mg/dL, the second week of 9.51 mg/dL and the third week 12.94 mg/dL with p-value 0.000 (p-0.05). Meanwhile, in a study by Hikmasari & Sari (2016), the decrease in blood glucose levels occurred only as an acute effect, but the chronic effect did not occur significantly after 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In physical exercise, blood flow will increase, causing more capillary nets to open so that more insulin receptors are available and the receptors become more active. This decrease in blood sugar levels is also related to an increase in the number and sensitivity of insulin receptors on cell membranes, so there is a 100% decrease in insulin requirements in people with Type II Diabetes Mellitus (Amelia et al, 2018).…”
Section: Langkat Regency In 2021mentioning
confidence: 99%